Tributyltin impacts in Galapagos Islands and Ecuadorian shore: Marine protected areas under threat. (July 2016) - Rodríguez Grimón, René Oscar; Arroyo Osorio, María Fernanda; de Freitas, Débora M.; Castro, Ítalo Braga
Abstract: Imposex incidence and biometric parameters were investigated in six muricid species along of 1200 km of Ecuadorian shore and in Galapagos archipelago. The obtained data, were compared to previous studies performed in the same area in 2009. The results showed that moderate imposex levels still occur in coastal areas of Ecuador, even after global TBT ban. However, a reduction in imposex parameters was detected in the sampled sites, indicating probably relationship to the global TBT ban issued by IMO at 2008. On the other hand, the levels currently reported in present study indicates that TBT environmental concentrations are still high enough to produce biological effects in studied areas. In addition, imposex incidence in four muricid species from Galapagos islands were detected suggesting that this marine protected area is under threat of antifouling contamination. These findings, after TBT global ban, denotes that current regulations and conservation plans still need to address such an issue and incorporate more restrictive management rules, particularly in complex coastal areas, vulnerable and unique systems such as the Galapagos Islands.